1-1THE EFFECT OF SIMVASTATIN FOR CAROTID INTIMA MEDIA THICKNESS IN ACUTE ISCHEMIC STROKE PATIENT WITH HYPERTENSION. (July 2020) - Kurnianto, Aditya; Tugasworo, Dodik
Abstract : Background: Acute ischemic stroke is caused by thrombotic or embolic occlusion of a cerebral artery. Carotid intima-media thickness (IMT) may be measured by ultrasound, where the distance between a double-line reflex pattern representing the luminal-intimal and the medial-adventitial interfaces corresponds well with IMT measured in histological specimens. Patients with hypertension tend to develop a thickening of the intima-media carotid artery. Simvastatin inhibits further atherothrombotic process. Objective: To analyze the effect of simvastatin for CIMT in ischemic stroke patient with hypertension. Method: This study was a Randomized Pretest-Posttest Design and conducted at the Hospital Inpatient Ward Dr Kariadi Semarang from January to December 2018 for all first ischemic stroke patients with hypertension treatment in Dr. Kariadi Hospital Semarang. Subjects were divided into groups of 35 controls, and 38 patients treated groups. The treatment group were given simvastatin 20 mg each daily for 24 weeks in 38 subjects with a history of acute ischemic stroke and hypertension. Examine the CIMT at the 1 st week and 24 th week. The normality of the data was tested using Shapiro Wilk and the differences analyzed by using Paired t-test. Result: There was a significant difference between CIMT on the administration of simvastatin for ischemic stroke patients with hypertension (p = 0, 04). Conclusion: Simvastatin significantly decreases CIMT on ischemic stroke patients with hypertension.